P17 Pharmacokinetics of macitentan in patients with portopulmonary hypertension: findings from the PORTICO sub-study. (December 2018) - Church, CA; Bosch, J; Cottreel, E; Csonka, D; Hoeper, M; Krowka, M; Martin, N; Kim, NH; Sitbon, O
Abstract : Introduction and objectives: Macitentan is an endothelin receptor antagonist approved for the treatment of pulmonary arterial hypertension (PAH). The PORTICO trial (NCT02382016 ) explored the efficacy and safety of macitentan in 85 patients with portopulmonary hypertension (PoPH), a population of patients in whom PAH is a complication of portal hypertension. In PORTICO, macitentan significantly improved pulmonary vascular resistance (PVR; primary endpoint; 35% reduction vs placebo), mean pulmonary artery pressure (mPAP) and cardiac index, with no hepatic safety concerns. The PORTICO pharmacokinetic (PK) sub-study explored the PK of macitentan and its active metabolite in patients with PoPH. Methods: PORTICO consisted of a 12 week randomised, double-blind, placebo-controlled treatment period, followed by a 12 week open-label treatment period during which all patients?received macitentan. Patients were aged ≥18 years and diagnosed with PoPH (PVR >320 dyn/sec/cm 5 ; mPAP ≥25 mmHg; pulmonary artery wedge pressure or left ventricular end diastolic pressure ≤15 mmHg), without severe hepatic impairment (defined as Child-Pugh class C or model for end-stage liver disease score ≥19). In the PK sub-study, a 24 hour PK profile was recorded at steady-state?after ≥4 weeks of open-label treatment with once-daily macitentan 10 mg. The PK analysis included patients who provided sufficient plasma samples for PK profile evaluation of macitentan and its active metabolite. Results: The PK sub-study was performed in ten patients; seven were male and the mean (standard deviation [SD]) age was 54.9 (8.6) years. The PK results for macitentan and its active metabolite in PORTICO were comparable with those reported in the PK sub-study of the Phase III SERAPHIN trial (NCT00660179 ) in patients with other forms of PAH (n=20) (table 1). Conclusion: The results from the PORTICO PK sub-study suggest that the steady-state exposure of macitentan and its active metabolite does not significantly differ between patients with PoPH or other forms of PAH. These findings are of relevance as they suggest that portal hypertension, and the liver disease that may be its underlying cause, does not affect the PK of macitentan or its active metabolite in patients with PoPH. Please refer to page A266 for declarations of interest related to this abstract.